Review on Classification, Methods, and Characterization of Polymeric Nanoparticles with Their Applications: Pharmaceutical Science-Pharmaceutics - Kumar Sharma, Dheerender; Thakur, Nishant; Deb, Barsha (International Journal of Life Science and Pharma Research, 2022)
The majority of this review’s emphasis is given to polymer-based nanoparticles, including their production, evaluation and their bioavailability. Biodegradable and biocompatible polymers of synthetic and natural origin make up the matrix of polymerbased nanoparticles. By reducing the size of the particles, polymer-based nanoparticles can significantly improve the solubility of poorly water-soluble drugs. Polymeric nanoparticles are excellent for directing a drug’s action at a particular spot. Additionally, polymeric nanoparticles are used to maintain and regulate the release of the drug. The kind of polymer that was employed to create the polymer-based nanoparticles is the subject of the current review study for their classification, characteristics, and applications of nanoparticles (NPs), which come in a variety of forms and sizes. Nanoparticles, which have diameters in the nm range, are the simplest type of structure. An NPs is well-defined as a collective group of molecules compelled composed of a structural range of fewer than 100nm. As of their higher solubility, smaller size, and improved penetrability, NPs are commonly used for a variety of dosage formulations. Some of the processes used to generate NPs include the Solvent Evaporation Method, Double Emulsion method, Salting Out Method, Precipitation Method, ionic gelation Method and Polymerization Method. The aim and objective of this review article is to give a concise information about polymeric nanoparticles including method of preparation and their applications.